2013
DOI: 10.1371/journal.pone.0061932
|View full text |Cite
|
Sign up to set email alerts
|

Lead Tolerance and Accumulation in Hirschfeldia incana, a Mediterranean Brassicaceae from Metalliferous Mine Spoils

Abstract: Lead is a heavy metal of particular concern with respect to environmental quality and health. The lack of plant species that accumulate and tolerate Pb is a limiting factor to understand the molecular mechanisms involved in Pb tolerance. In this study we identified Hirschfeldia incana, a Brassicaceae collected from metalliferous mine spoils in Morocco, as a Pb accumulator plant. H. incana exhibited high Pb accumulation in mine soils and in hydroponic cultures. Major Pb accumulation occurred in the roots and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 51 publications
(60 reference statements)
2
30
0
Order By: Relevance
“…salviifolius (Figure 2b), showing that the roots of all three species accumulated much more Pb than their aboveground parts. A similar trend has been observed in C. ladanifer (Kidd et al, 2004) and H. incana roots (Auguy et al, 2013; Fahr et al, 2015). This is a general pattern of Pb distribution in plants (Pourrut et al, 2011), possibly due to binding of Pb in cell wall polysaccharides of root cells (Fahr et al, 2013; Seregin & Ivanov, 1998).…”
Section: Resultssupporting
confidence: 79%
“…salviifolius (Figure 2b), showing that the roots of all three species accumulated much more Pb than their aboveground parts. A similar trend has been observed in C. ladanifer (Kidd et al, 2004) and H. incana roots (Auguy et al, 2013; Fahr et al, 2015). This is a general pattern of Pb distribution in plants (Pourrut et al, 2011), possibly due to binding of Pb in cell wall polysaccharides of root cells (Fahr et al, 2013; Seregin & Ivanov, 1998).…”
Section: Resultssupporting
confidence: 79%
“…It plays a role in metal homeostasis during seed development and seed germination rather than in metal decontamination (Roosens et al, 2004 ; Maestri et al, 2010 ). The analysis of the expression of MT2a in A. thaliana , a non-Pb tolerant species, showed that were specifically over-expressed in roots by Pb-treatment (Auguy et al, 2013 ). MTs are extremely diverse in plants and T. caerulescens seems to be an excellent model to understand the adaptive significance of this phenomenon.…”
Section: Thiol-compounds and Metal(loid)-chelationmentioning
confidence: 99%
“…Of about 450 plant species reported worldwide for phytoextraction, few of them are Pb hyperaccumulators while majority are for nickel and zinc. Knowledge on the application of phytoextraction strategy for the remediation of Pb-contaminated soils is therefore lacking [28,31]. This has been identified as a limiting factor in studying and understanding the molecular and genetic mechanisms involved in Pb tolerance [28].…”
Section: Introductionmentioning
confidence: 99%